Granulosa Cells Improved Mare Oocyte Cytoplasmic Maturation by Providing Collagens - Zhu, Xinyuan; Zhao, Shanshan; Xu, Shibo; Zhang, Dongyu; Zhu, Minghui; Pan, Qingjie; Huang, Jiaojiao (Frontiers in Cell and Developmental Biology, 2022)
Assisted reproductive technology has important clinical applications and commercial values in the horse industry. However, this approach is limited largely by the low efficiency of oocyte in vitro maturation (IVM), especially cytoplasmic maturation. To improve the efficiency of mare oocyte IVM, we evaluated the effects of co-culture with cumulus–oocyte complexes (COC) and granulosa cells (GCs) from follicles with small (<15 mm) and large diameters (>35 mm). Our results showed that oocyte nucleus maturation was not significantly improved by co-culturing with GCs. Interestingly, the cytoplasmic maturation of oocytes, defined by the distribution of cortical granules and mitochondria, as well as reactive oxygen species (ROS) levels, improved dramatically by co-culture with GCs, especially those derived from small follicles. Moreover, GCs promoted cumulus cell expansion by up-regulating the expression of BMP15 in oocytes. To determine the mechanism underlying the effects of GCs, the transcriptomes of GCs from large and small follicles were compared. Expression levels of COL1A2, COL6A1, and COL6A2 were significantly higher in GCs from small follicles than in those from large follicles. These three genes were enriched in the extracellular matrix proteins-receptor interaction pathway and were involved in the regulation of collagens. Taken together, our results suggest that co-culture with GCs is beneficial to oocyte cytoplasmic maturation, and the increased expression of COL1A2, COL6A1 and COL6A2 improve the mare oocyte IVM system via the regulation of collagen.